ZAHIRIDDIN MUHAMMAD BABUR'S PRINCIPLES OF JUSTICE AND RULE OF LAW IN PUBLIC ADMINISTRATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article presents information on the principles of justice and the rule of law in public administration of Zahiriddin Muhammad Babur.